PENERAPAN STRATEGI PEMBELAJARAN SAINTIFIK DALAM MENGEMBANGKAN ASPEK BAHASA ANAK USIA DINI DI KELOMPOK BERMAIN MUTIARA BUNDA - Afnita Handayani; Susanti Nirmalasari; Hasnah Siahaan (HIBRUL ULAMA, 2025)
Language development is one of the fundamental abilities that must be nurtured in early childhood because it underlies communication and social interaction. This study aims to describe the application of a scientific learning strategy in developing the language aspect of early childhood at Kelompok Bermain Mutiara Bunda, Makmur Village, Teluk Mengkudu Subdistrict, Serdang Bedagai Regency. A qualitative descriptive method with a field research design was used, involving six children aged 4-5 years selected purposively from a population of eighteen children as the source of secondary data, supported by observation, interviews, and documentation with teachers and parents. Data were analyzed descriptively based on the stages of the scientific approach, namely observing, questioning, gathering information, associating, and communicating. The results show that the strategy, implemented through lining up and observing the surroundings, storytelling, conversing about daily topics, and recognizing letters and numbers, was able to enrich children's vocabulary and encourage them to speak and ask questions more actively. Overall, children's language development reached the developing as expected (BSH) category, although the indicators of understanding simultaneous commands and distinguishing letters and numbers were still at the starting to develop (MB) stage, and family and peer environment were found to strongly influence the results. This study concludes that the scientific learning strategy is effective in developing early childhood language and recommends closer collaboration between teachers and parents to optimize children's language stimulation.